Eficácia da norma coletiva à luz do princípio da autonomia da vontade - Hasegawa, Jamille Ribeiro Pires (2019)
After the Industrial Revolution, the inequalities between the subjects of the employment relationship became evident. The constant concern with this inequality has translated into a model of labor contract in which the state actively participates in its clauses, leaving minimal possibilities for the parties to exercise their autonomy of will. The modern world, however, has forced society into new models of employment relationships, where subordination, which is most responsible for state intervention, no longer has the same force. Given these circumstances, it became imperative to recognize the fruits of collective bargaining as authentic sources of law, assuring them the full exercise of the autonomy of will. In turn, the inability of the consolidated legislation to discipline the new economic realities requires the restructuring of conflicts between law and collective bargaining, questioning the effectiveness of the principle of the most favorable norm. Collective bargaining, as a natural alternative to the slowness of the legislative process and the fragility of the uniquely considered employee, is very appropriate for self-regulation of working conditions. In this sense, Law No. 13.467 / 2017, also known as Labor Reform, effective as of November 11, 2017, brought some changes to the text of Decree-Law No. 5,452, of May 1, 1943, ensuring greater freedom for women. parties during collective bargaining, while also ensuring the minimum intervention of the judiciary in the autonomy of the collective will. The present research proposes, thus, the strengthening of collective relations, in order to recognize to the social actors the possibility of flexibilizing the legislation in pejus, in face of the concrete necessities of each work relation, having to prevail the negotiated one over the legislated one, since the legal requirements of the legal business, provided for in art. 104 of the Brazilian Civil Code